The Use of the Bible in Modern Court System: A Critique of the Appropriateness of the Practice - Abraham Nortey (E-Journal of Religious and Theological Studies)
The study examines the practice of using the Bible to swear in the law court. It exposes biblical texts that speak about swearing of oath and taking vows. Since this is an ongoing debate, the paper raises scholarly opinions that support and speak against the practices by examining their theological basis for doing so. The goal of this research is to highlight the consequences associated with swearing with a sacred book considered the words of a just God. The research is a literary one. It uses textual analyses of selected biblical passages and critiques various theological positions on the subject by some selected denominations and theologians to propose a review of the practice. Specific attention will be given to key but controversial biblical passages in Genesis 24: 2-3, Matthew 5:34-37 and James 5:12 on oath- taking that has generated varied responses. The study establishes that for the Bible to be used in court the lawmakers should establish their position on certain biblical laws on crime and their implications by working hand in hand with God-fearing theologians. Once such statements of faith are added to the laws or constitution it will authenticate the need to use the bible to swear. The researcher has observed that since the judgment of court cases do not impinge on the content of the Bible, the practice is not helpful in adjudication. It rather ends up profaning the name of God in case witnesses lie in court. One would therefore propose that those who are occupying office for the first time could swear with the Bible as a way of asking God to help them discharge their functions well.